PENGARUH DARI BERHENTINYA BAMIKRO DI SEMBARANG TEMPAT PADA ARUS LALU LINTAS - Abdurrahman Abdurrahman (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
City transportation in Banjarmasin is called Bamikro or Banjarmasin Mikrolet serves passenger transportation that consists of several types of cars / vehicles. The operation of this vehicle to serve the passengers is a problem for other vehicles. They often stop abruptly and do not attempt to pulll over the vehicle; have the passengers get into and off arbitrarily and often do not stop at the spots which have been provided (shelter). As a consequence of this vehicle, other road users’ forward movements behind it are interrupted. This vehicle tries to take the lane of another vehicle, causing a narrowing in a way resulting in disruption of roads taken and if it cannot take another lane because the lane is filled, then the vehicle is forced to stop for the completion of Bamikro to serve passengers. The length of the delay of the vehicles by the operation of Bamikro are calculated and the data collected and used in the calculation were obtained from the survey of traffic on the road segment by determining the result of (i) the percentage of Bamikro in traffic flow (ii) the frequency and duration of the stoppage. Keywords: Bamikro, Shelter, Frequency